The Influence of Animal Phobia on Post-Traumatic Stress Disorder (PTSD) - Ngamcha Roensukphon (Multidisciplinary Journal of Akseprin Indonesia, 2025)
The apprehension over animals in urban settings has emerged as a significant concern, particularly in highly populated regions such as Bangkok. With the expansion of urbanization, interactions between humans and wildlife have increased, frequently eliciting extreme fear responses that may lead to mental health issues. This study seeks to investigate the correlation between animal phobia and symptoms of Post-Traumatic Stress Disorder (PTSD), along with its effects on daily activities among inhabitants of Bangkok. We employed a standardized questionnaire to gather responses from 360 participants, assessing the impact of PTSD on everyday activities in relation to fear of animals. Our findings indicate that interactions with animals may lead to psychological anguish, with women possibly being more impacted. A plausible explanation is that elevated estrogen levels in women may heighten sensitivity to stress and emotional recollection, while testosterone in men may stabilize stress responses. This underscores the necessity of comprehending human-animal interactions in urban environments, which could guide mental health support and associated policies. These findings necessitate the examination of gender and hormonal variations in comprehending stress reactions and psychological health during animal interactions to enhance mental well-being